Fusion-positive skin/adnexal carcinomas - Agaimy, Abbas (Genes Chromosomes & Cancer, 2022)
Gene fusions have been increasingly identified as central events driving oncogenesis in a variety of benign and malignant neoplasms of different histogenesis originating in diverse organs. While some fusion-driven neoplasms may occur at any body site, certain genotypes and their associated phenotypic entities cluster to specific body site/organ, albeit with variable frequencies among anatomic locations. In the last two decades, several skin adnexal entities driven by specific fusions have been described; some of them represent new entities (eg, secretory carcinoma harboring NTRK fusions), while others are old established entities with newly discovered underlying gene fusions (eg, poroid neoplasms harboring NUTM1, YAP1, and WWTR1 fusions). While limited availability of next generation sequencing tools in routine practice has largely limited and delayed discovery of fusions in old entities, the increasing availability of novel immunoantibodies as surrogates to recognize gene fusions (such as NUT and YAP1 immunohistochemistry) represents a relatively cheap, quick, and reliable routine tool for their proper recognition and appropriate classification. This review highlights the main, recently defined skin adnexal carcinomas carrying gene fusions.
CRIS-Team Scopus Importer:2022-03-11
Keywords: adnexal carcinoma; gene fusion; NUT carcinoma; NUTM1; porocarcinoma; poroma; YAP1